Enteropathogenic Escherichia coli (EPEC): Does it have a role in colorectal tumourigenesis? A Prospective Cohort Study. (June 2015) - Magdy, A.; Elhadidy, M.; Abd Ellatif, M.E.; El Nakeeb, A.; Abdallah, E.; Thabet, W.; Youssef, M.; Khafagy, W.; Morshed, M.; Farid, M.
Abstract: Background: Despite the characterization of many aetiologic genetic changes. The specific causative factors in the development of sporadic colorectal cancer remain unclear. This study was performed to detect the possible role of Enteropathogenic Escherichia coli (EPEC) in developing colorectal carcinoma. Patients and method: Fresh biopsy specimens have been obtained from the colonic mucosa overlying the colorectal cancer as well as from the colon of the healthy controls. Culture, genotyping and virulence of EPEC were done using (nutrient broth culture, and PCR). Strains biochemically identified as Escherichia coli were selected from the surface of a MacConkey's plate and were serogrouped by slide agglutination tests. Results: From January 2011 to June 2014, 213 colorectal cancer patients (Group 1) and 248 healthy controls (Group 2) were prospectively enrolled in this study. EPEC was positive in 108 (50.7%) in group 1 and 51 (20.6%) in group 2 (P = 0.0001). A significant difference between both groups was observed regarding serotyping, genotyping (eae gene) and virulence category (P = 0.0001). A significant difference between the 2 subgroups of colorectal cancer cases was observed regarding genotyping (eae, bfb genes) and virulence category. Conclusion: The incidence EPEC was higher significantly in patients with colorectal cancer. E. coli in patients with colorectal cancer significantly differed serotypically and genotypically from the E. coli in normal population. E. coli colonization of the colonic mucosa may be a cause colorectal cancer. Highlights: we highlight the tumorigenic role of Enteropathogenic Escherichia coli (EPEC). We aimed to see if it has role in colorectal cancer development. By genetic study of colonic mucosa from patents and normal.